BANKING INVESTMENT LENDING IN CONDITIONS OF IMBALANCES OF MOVEMENTS OF FINANCIAL RESOURCES - Alina Herasymenko (Baltic Journal of Economic Studies, 2016)
The purpose of the paper is to justify theoretically the existence of disparities between the paces of development of the financial and real sectors of the economy of Ukraine, and in this regard, to study of the role of the banking investment lending as a credit instrument in managing imbalances of movement of financial resources. The hypothetico-deductive method allows us to investigate the causes of occurrence of disparities between the rates of development of the financial and real sectors of the Ukrainian economy. The method of analysis allows us to investigate the penetration rate of bank credit mechanisms in the past five years (2011-2015) in the processes of financing of the needs of the real sector for capital investments. Methodology. The survey is based on the theoretical analysis of the scientific literature in order to identify the causes of imbalances of movement of financial resources, the result of their influence on the pace of development of the real and financial sectors of the economy. The work displays the main approaches to the definition of the term of "financialization". Different points of view of scientists about the impact of financialization on investment processes and the flow of financial resources are grouped in this article. Also, there are presented visions of the major economic schools on the interaction of financial and real sectors of the economy. On the basis of special non-fiction the author of this research worked out the simplified scheme of imbalances of movement of financial resources in the economy. Also, in this article are studied the theoretical basis of bank investment lending, and is justified its role in managing the process of convergence of the financial and real sectors of the economy. Results of the survey showed that the cause of the imbalances of movement of financial resources is the processes of financialization. This process leads to distortion of the key role of the financial sector, which is to serve the real sector. Banking investment lending may be an effective mechanism for the convergence of the financial and the real sector. However, the result of analysis has shown that it does not work in modern conditions. Practical implications. The theoretical and practical analysis can be the basis for future research, especially with regards to the reasons of non-usage of banking investment lending as a tool of the control of imbalances of movement of financial resources in terms of prevailing financial sector relative to the real. Value/ originality. The results of the study make it possible to provide a better understanding of the role and practical importance of banking lending as a tool of investment in real sector, which is used by banks with the purpose to control the motions of financial resources.